Of mice and men: modelling post-stroke depression experimentally - Kronenberg, G (BlackWell Publishing Ltd, 2014)
At least one-third of stroke survivors suffer from depression. The development of comorbid depression after stroke is clinically highly significant because post-stroke depression is associated with increased mortality, slows recovery and leads to worse functional outcomes. Here, we review the evidence that post-stroke depression can be effectively modelled in experimental rodents via a variety of approaches. This opens an exciting new window onto the neurobiology of depression and permits probing potential underlying mechanisms such as disturbed cellular plasticity, neuroendocrine dysregulation, neuroinflammation, and neurodegeneration in a novel context. From the point of view of translational stroke research, extending the scope of experimental investigations beyond the study of short-term end points and, in particular, acute lesion size, may help improve the relevance of preclinical results to human disease. Furthermore, accumulating evidence from both clinical and experimental studies offers the tantalizing prospect of 5-hydroxytryptaminergic antidepressants as the first pharmacological therapy for stroke that would be available during the subacute and chronic phases of recovery. Interdisciplinary neuropsychiatric research will be called on to dissect the mechanisms underpinning the beneficial effects of antidepressants on stroke recovery. LINKED ARTICLES: This article is part of a themed section on Animal Models in Psychiatry Research. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2014.171.issue-20